Peranan Sungai Musi Dalam Pembangunan Ekonomi di Sumatera Selatan: Perspektif Sejarah dan Geografi - Wijaya, Tomy; Alauwiyah, Fatimah; Nurrohma, Devinna; Safitri, Sani; Oktapiani, Rani (Historis : Jurnal Kajian, Penelitian dan Pengembangan Pendidikan Sejarah, 2025)
Musi River has a strategic role in the regional economic development of South Sumatra since the Sriwijaya Kingdom until the modern era. In addition, the Musi River is the main transportation route in South Sumatra. The river also supports trade, distribution of goods, as well as the development of tourism and culture-based creative economy. This research aims to analyze the role of the Musi River from the perspective of history and geography in supporting the regional economy. This research uses a literature study method with a qualitative descriptive approach to examine various written sources related to the history, transportation, trade, and tourism of the Musi River. Data was collected from journal articles, books, and official photographs to obtain a comprehensive analysis. The results show that the Musi River contributes significantly to domestic and export trade, especially through the Boom Baru port. In addition, the potential for water tourism and cultural festivals supports the development of the creative economy. However, challenges such as sedimentation and infrastructure modernization still need to be addressed. Therefore, further research is needed to optimize the sustainable use of the Musi River for South Sumatra's economic growth.